Association of glycated albumin with the presence of carotid plaque in patients with type 2 diabetes. Issue 6 (3rd June 2013) - Sato, Yuki; Nagao, Mototsugu; Asai, Akira; Nakajima, Yasushi; Takaya, Makiyo; Takeichi, Naomi; Takemitsu, Shuji; Sudo, Mariko; Kano‐Wakakuri, Toshiko; Ishizaki, Akira; Harada, Taro; Tanimura‐Inagaki, Kyoko; et al.
Abstract Aims/Introduction Postprandial hyperglycemia is a potent risk factor for cardiovascular disease. Serum glycated albumin (GA) has been reported to reflect postprandial blood glucose fluctuations. In the present study, we assessed the possible correlation of GA with the presence of carotid plaque to evaluate the potential clinical usefulness of GA for predicting atherosclerotic cardiovascular complications in patients with type 2 diabetes. Materials and Methods Patients with type 2 diabetes (n = 236) admitted to Nippon Medical School Hospital (Tokyo, Japan) for glycemic control (aged 19–86 years, 81 females and 155 males) were examined. Clinical measurements were taken on admission. The presence of carotid plaque was assessed by ultrasonography. Results In patients with carotid plaque (n = 154), GA (P = 0.023) was higher than those without carotid plaque (n = 82). In contrast, neither fasting plasma glucose (P = 0.48) nor glycated hemoglobin (P = 0.41) was significantly different between the groups. The results of logistic regression analysis showed that GA (age‐ and sex‐adjusted odds ratio [95% confidence interval], 1.05 [1.01–1.09]; P = 0.017) and glycated hemoglobin (1.17 [1.01–1.37]; P = 0.036) were significantly associated with the presence of carotid plaque. Conclusions The positive correlation of serum GA with the presence of carotid plaque in type 2 diabetes suggests that GA will serve as a useful clinical marker for predicting diabetic cardiovascular complications.